Out-of-plane interactive behavior and design of novel T-hooked buckling-restrained steel plate shear walls - Wang, Ling-Qi; Wang, Hai-Shan; Hou, Jian; Tong, Jing-Zhong; Wu, Ruo-Min; Li, Qing-Hua; Xu, Shi-Lang (Structures (Oxford), 2024)
To eliminate the use of a large number of connecting bolts for the cover panels in conventional buckling-restrained steel plate shear walls (BRSPSWs), T-hooked BRSPSW was proposed by using T-sectional stiffeners for restraining the out-of-plane deformation of the cover panels. With larger-sized flexural cover panels that provide confinement effects to the infilled steel plate, the out-of-plane interactive behavior between the infilled steel plate and each cover panel is greatly concerned for safe designs of the T-hooked BRSPSW. In this paper, a refined finite element (FE) model was established for evaluating the out-of-plane restraining effects in the T-hooked BRSPSW. The key parameters affecting the high-order buckling modes of the infilled steel plate were analyzed. The average spacing between adjacent buckling half-waves varied from 0.15 to 0.7 times the height of the steel sub-plate across common parameter ranges. Furthermore, a formula that estimates the total extrusion force produced by the buckled steel plate was corrected. By simplifying the cover panels into one-way flexural plates under uniform force, a flexural moment amplification coefficient in the range of 1.11 − 9.74 was defined to consider the difference between the actual strip-shaped interaction forces and the simplified model. Finally, a formula to calculate the bending moment of cover panels was proposed to safely design the T-hooked BRSPSWs.